Examination of Affective Responses to Images in Sponsorship-Linked Marketing. Issue 3 (1st October 2016) - Cornwell, T. Bettina; Lipp, Ottmar V.; Purkis, Helena
ABSTRACT: Sponsorship of sports, arts, charity and entertainment events are all viewed as capable in building corporate and brand image. In this process, visual images are a key vehicle in the transportation of affect from an event to a brand. While the overall positive feeling of a sponsored event or activity is argued to rub-off on a brand, we know less about how individual images function in this process and we know even less about the role of negative images. Here, three experiments consider the potential of affect transfer from images to brands. All three experiments show explicit transfer of affect, and one finds implicit evaluative change. Importantly, positive images when mixed with negative are off-setting. This research suggests that when negative events occur and are captured and repeated in the media, practitioners able to supply positive images may be able to control negative affective responses to some degree.